2022
DOI: 10.3390/ijerph19020818
|View full text |Cite
|
Sign up to set email alerts
|

Relative Effectiveness of Cell-Cultured versus Egg-Based Seasonal Influenza Vaccines in Preventing Influenza-Related Outcomes in Subjects 18 Years Old or Older: A Systematic Review and Meta-Analysis

Abstract: Avian mutations in vaccine strains obtained from embryonated eggs could impair vaccine effectiveness. We performed a systematic review and meta-analysis of the adjusted relative vaccine effectiveness (arVE) of seed cell-cultured influenza vaccines (ccIV) compared to egg-based influenza vaccines (eIV) in preventing laboratory-confirmed influenza related outcomes (IRO) or IRO by clinical codes, in subjects 18 and over. We completed the literature search in January 2021; applied exclusion criteria, evaluated risk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
3
11
0
Order By: Relevance
“…Influenza infections in children and adults <65 years of age account for an estimated annual average economic burden of $1.84 billion in direct medical expenditures and $6.94 billion in indirect costs due to missed school by sick children and missed work by sick adults and the parents and guardians who care for children with influenza [54,55]. The results discussed in this review are part of a broader set of studies that have evaluated the relative vaccine effectiveness and cost effectiveness of IIV4c compared to IIV4e [27,[56][57][58][59]. The use of RWE to assess rVE will remain an important source of data for the timely assessment of current and future seasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influenza infections in children and adults <65 years of age account for an estimated annual average economic burden of $1.84 billion in direct medical expenditures and $6.94 billion in indirect costs due to missed school by sick children and missed work by sick adults and the parents and guardians who care for children with influenza [54,55]. The results discussed in this review are part of a broader set of studies that have evaluated the relative vaccine effectiveness and cost effectiveness of IIV4c compared to IIV4e [27,[56][57][58][59]. The use of RWE to assess rVE will remain an important source of data for the timely assessment of current and future seasons.…”
Section: Discussionmentioning
confidence: 99%
“…While the RWE evaluations of the rVE of IIV4c versus IIV4e may be best done in the context of the entire available body of evidence, disentangling the relative contributions of study design and season-specific effects on variations in the observed rVE presents a complex challenge. The rVE of IIV4c versus IIV4e has already been evaluated using a systematic literature review and meta-analysis approach [27]. In this review, the use of the same methodologies and databases across each season allow for the evaluation of how the differences in the underlying epidemiological characteristics of the influenza seasons may have contributed to variation in the rVE of IIV4c versus IIV4e.…”
Section: Real-world Evidencementioning
confidence: 99%
“…Evidence from real-world, observational studies and randomized controlled trials supports the negative impact of egg adaptation on the level of protection offered by influenza vaccines. Across multiple real-world observational studies spanning different seasons comparing the effectiveness of egg- and cell-based influenza vaccines, cell-based vaccines have generally been found to be more effective than egg-based vaccines, particularly in adults 18–64 years of age [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. A recent meta-analysis of observational studies conducted during the 2017–2018 and 2018–2019 influenza seasons highlights the potential impact of egg adaptation vs. antigenic drift on vaccine effectiveness [ 40 ].…”
Section: Mutations In Cell-based and Egg-based Cvv Isolates And Impli...mentioning
confidence: 99%
“…Across multiple real-world observational studies spanning different seasons comparing the effectiveness of egg- and cell-based influenza vaccines, cell-based vaccines have generally been found to be more effective than egg-based vaccines, particularly in adults 18–64 years of age [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. A recent meta-analysis of observational studies conducted during the 2017–2018 and 2018–2019 influenza seasons highlights the potential impact of egg adaptation vs. antigenic drift on vaccine effectiveness [ 40 ]. The 2017–2018 season was characterized by significant A/H3N2 egg adaptation and was also a high-severity influenza season [ 22 ].…”
Section: Mutations In Cell-based and Egg-based Cvv Isolates And Impli...mentioning
confidence: 99%
See 1 more Smart Citation